1987
DOI: 10.1002/1097-0142(19870115)59:2<245::aid-cncr2820590212>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy for carcinomatous peritonitis and pleuritis with MMC-CH, mitomycin C adsorbed on activated carbon particles. Clinical trials

Abstract: A new drug dosage form comprising activated carbon particles adsorbing mitomycin C (MMC-CH) is designed to slowly release its components, and has affinity for the tumor surface and lymph nodes and a tendency to stay long in the local portion. The therapeutic index of MMC-CH in experimental carcinomatous peritonitis is 3.1 times as high as that of MMC-solution. In clinical experiments 81 patients with carci-nomatous effusions were administered with MMC-CH (2.0-2.4 mg/kg in terms of MMC) in bolus in-tracavitaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…To overcome these drawbacks, the targeting of anticancer drugs with various types of drug carriers has thus been investigated. [12][13][14] With the advent of monoclonal antibody technology, the use of antibodies as carriers of pharmacological agents has become more practical, and several studies have therefore demonstrated the potential clinical feasibility of immunoconjugates. 4,15 The main factors allowing a MoAb and anti-cancer drug conjugate to be effective on cancer cells are their high cytotoxic potency and a high selective binding activity of the immunoconjugates to the target cancer cells.…”
supporting
confidence: 86%
“…To overcome these drawbacks, the targeting of anticancer drugs with various types of drug carriers has thus been investigated. [12][13][14] With the advent of monoclonal antibody technology, the use of antibodies as carriers of pharmacological agents has become more practical, and several studies have therefore demonstrated the potential clinical feasibility of immunoconjugates. 4,15 The main factors allowing a MoAb and anti-cancer drug conjugate to be effective on cancer cells are their high cytotoxic potency and a high selective binding activity of the immunoconjugates to the target cancer cells.…”
supporting
confidence: 86%
“…Up to now, most oncologists would regard them as a situation only to be palliated. Intraperitoneal injection of anticancer drugs, such as OK 432 4 or mitomycin C (MMC) absorbed on activated charcoal, 5 has been used, but the effectiveness of this approach has not been well established. Research protocols, including immediate postoperative intraperitoneal chemotherapy and extended peritonectomy, 6 are currently ongoing.…”
mentioning
confidence: 99%
“…order to obtain the best fit for the estimates of K D and K i. The values obtained (Table 1) were in conformity with those reported in the literature [9,11,13,14].…”
Section: Methodsmentioning
confidence: 99%
“…In the sustained-release formulation the drug was preadsorbed onto 120 mg activated charcoal [11,12].…”
Section: Formulationsmentioning
confidence: 99%